(untitled) (Historia, 2021)
In a secluded portion of thf!’ Military Cemetery at Fort Napier, Pieter-maritzburg, amidst the graves of numerous British soldiers who died in Natal,high ranking officers and privates alike, lies the grave of Walter Harding, thelilst r;esting place of one of the pi neers of Natal, and one who made alasting mark on the small colony during a large portion of the nineteenthcentury.rhis article i an /!.ttempt to bring Walter Harding, the man, intocorrect perspective in relation to his day, and also to assess his achievementsin the sphere in which he lived.Little is known of the place or date of birth of Walter Harding and thepresent, writer has searched unavailingly for information. As will be seenlater there was some confusion at 1he time of his death about his correctage. But it is certain that Walter Harding was the son of William WalterHarding (1782-1831) and Eliza Herrick (1793-1866) ,1William Walter Harding purchased an ensigncy in the 20th Regimentof Foot in;1800, and also promotion to the rank of Lieutenant (.25-6-1803)and Captain (12-10-1809) and took part in the Allied campaign againstN poleon, doing service in’ Egypt and Spain.2IQ November 1811 William Harding transferred to the Cape Corps andretired from the army in June 1819 by selling his commission.3 This salecaused some comment at the time and it has since come to light that the saleof Harding’s commission had been strongly urged by the then Governor atthe Cape, Lord Charles Somerset!Soon after his retirement from the army, William Harding obtainedt e post of Deputy Landdrost- at Cradock, but he soon relinquished the poston account of bad health. He thereafter held the posts of Resident Magis-trate, Beaufort West (1-1-1828), Justice of the Peace at Graaff-Reinet(19-6-1828), Resident Magistrate, Swellendam (10-12-1828), Justice of thePeace, Swellendam (28-2-1829) and Resident Magistrate and Justice of thePeace at Uitenhage, at which latter place he died on 27-3-183